INFORMATION AND LASER TECHNOLOGIES FOR ASSESSING THE LEVEL OF RISKS FROM HARMFUL EMISSIONS FROM MAN-MADE OBJECTS - SIKORA, Liubomyr; LYSA, Nataliia; FEDEVYCH, Olga; KHYLIAK, Nazarii (Computer systems and information technologies, 2025)
The current stage of development of electricity, chemical, machine-building, and printing production is characterized by the use of a wide range of resource components - coal, oil, gas, paints, and polymers - that are environmentally aggressive. The intense production regimes which are dictated by the market lead to a sharp increase in resource consumption for energy-intensive production processes, causing, in turn, an increase in the concentration of dust and harmful gases and liquid emissions into the atmosphere and water environment, which leads to an increase in environmental pollution, the state of which cannot always be assessed in real time due to the complexity of data collection using standard methods. The article substantiates the methods of creating sensors for measuring the concentration of dust and harmful substances emissions into the atmosphere and water environments using new physical effects that became the basis for the development of laser concentrators of air and water pollution, optogalvanic effects for creating integrated sensors that can be combined with measurement systems based on ion-selective sensors (OCS 5M), which makes it possible to increase the level of efficiency of environmental safety systems. A comprehensive solution to the problem is based on the creation of global environmental monitoring systems based on information and intellectual technologies and the development of new sensor models. The problem of environmental monitoring has been relevant for more than a century, because of the development of industrial technologies (railroads, weaving) has brought not only prosperity but also environ-mental pollution. The level of environmental pollution has increased especially with the development of thermal power plants and the petrochemical complex, which have become aggressive polluters. The military operations of the First and Second World Wars also contributed to this. Nuclear power and jet aviation have further polluted the global environment, and the war in Ukraine has created a specific environmental impact (explosions of shells and missiles), destruction of energy complexes and oil terminals.